2016
DOI: 10.1111/1365-2435.12809
|View full text |Cite
|
Sign up to set email alerts
|

Landscape impacts on pollinator communities in temperate systems: evidence and knowledge gaps

Abstract: Summary1. This review assesses current knowledge about the interplay between landscape and pollinator communities. Our primary aim is to provide an evidence base, identify key gaps in knowledge and highlight initiatives that will help develop and improve strategies for pollinator conservation. 2. Human-dominated landscapes (such as arable land and urban environments) can have detrimental impacts on pollinator communities but these negative effects can be ameliorated by proximity to semi-natural habitat and hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
138
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 94 publications
3
138
0
2
Order By: Relevance
“…, Senapathi et al. ). Additionally, pollinator communities need these resources to be temporally distributed (Leong et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Senapathi et al. ). Additionally, pollinator communities need these resources to be temporally distributed (Leong et al.…”
Section: Discussionmentioning
confidence: 99%
“…The stronger decrease suggested for Bombus bumblebees is surprising, given that bumblebee densities and presences are assumed not to be determined by very local landscape characteristic and can benefit from urbanization (Carré et al, ; Kennedy et al, ; Senapathi, Goddard, Kunin, & Baldock, ). However, bumblebees might show an elevated susceptibility to rapid climate change (Kerr et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Pollination efficiency of different crops is strongly related to wild bee species diversity (Földesi et al, ; Winfree et al, ) as well as functional diversity (Fontaine et al, ; Garibaldi et al, ). Research demonstrated that wild bees are threatened by intensive agricultural practices (Kremen, Williams, & Thorp, ) such as high pesticide application (Woodcock et al, ), and/or frequent soil tillage (Williams et al, ), which result in reduction of floral resource availability (Williams et al, ) and contribute to landscape simplification (Senapathi, Goddard, Kunin, & Baldock, ).…”
Section: Introductionmentioning
confidence: 99%